2015
DOI: 10.2147/cia.s72348
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral activation for dementia caregivers: scheduling pleasant events and enhancing communications

Abstract: BackgroundDementia caregiving is often associated with increase in depressive symptoms and strained relationships. This study tested whether telephone-delivered psychoeducation combined with an enhanced behavioral activation (BA) module had a better effect on the well-being of Alzheimer’s caregivers than psychoeducation alone. The focus is on enhancing the competent use of coping skills via BA. The program is delivered by telephone to increase accessibility and sustainability for caregivers. Senior citizens ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 29 publications
0
63
0
2
Order By: Relevance
“…The interventions included in this review varied in their composition of strategies (Table ). The most common categories that components fell under include: education and skills training (Au et al ., ; Beauchamp et al ., ; Belle et al ., ; Czaja et al ., ; Elliott et al ., ; Gitlin et al ., , ; Gonyea, O'Connor & Boyle, ; Hepburn et al ., ; Kurz, Wagenpfeil, Hallauer, Schneider‐Schelte & Jansen, ; Marriott, Donaldson, Tarrier & Burns, ; Steffen, ; Waldorff et al ., ), counselling (Connell & Janevic, ; Drentea et al ., ; Mittelman et al ., , , , ; Roth et al ., ; Waldorff et al ., ) and support groups (Belle et al .; Czaja et al .; Drentea et al ., ; Elliott et al .; Mittelman et al .; Roth et al ., ). Other less common components fell under the following categories: stress management (Belle et al .; Elliott et al .; Marriott et al .; Steffen), exercise and health promotion (Belle et al .; Connell & Janevic; Elliott et al .), computerised telephone support system linking caregivers to therapy sessions and community resources (Belle et al .; Eisdorfer et al ., ; Elliott et al .), role play (Belle et al .; Elliott et al .), and environmental modification (Gitlin et al .; Horvath et al ., ).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The interventions included in this review varied in their composition of strategies (Table ). The most common categories that components fell under include: education and skills training (Au et al ., ; Beauchamp et al ., ; Belle et al ., ; Czaja et al ., ; Elliott et al ., ; Gitlin et al ., , ; Gonyea, O'Connor & Boyle, ; Hepburn et al ., ; Kurz, Wagenpfeil, Hallauer, Schneider‐Schelte & Jansen, ; Marriott, Donaldson, Tarrier & Burns, ; Steffen, ; Waldorff et al ., ), counselling (Connell & Janevic, ; Drentea et al ., ; Mittelman et al ., , , , ; Roth et al ., ; Waldorff et al ., ) and support groups (Belle et al .; Czaja et al .; Drentea et al ., ; Elliott et al .; Mittelman et al .; Roth et al ., ). Other less common components fell under the following categories: stress management (Belle et al .; Elliott et al .; Marriott et al .; Steffen), exercise and health promotion (Belle et al .; Connell & Janevic; Elliott et al .), computerised telephone support system linking caregivers to therapy sessions and community resources (Belle et al .; Eisdorfer et al ., ; Elliott et al .), role play (Belle et al .; Elliott et al .), and environmental modification (Gitlin et al .; Horvath et al ., ).…”
Section: Resultsmentioning
confidence: 98%
“…One study reported that caregivers worked in part‐time jobs (Beauchamp, Irvine, Seeley & Johnson, ). Fifteen studies included family caregivers (Au et al ., ; Beauchamp et al .; Belle et al .; Connell & Janevic, ; Czaja et al .; Drentea, Clay, Roth & Mittelman, ; Eisdorfer et al .; Elliott et al .; Hepburn, Tornatore, Center & Ostwald, ; Horvath et al ., ; Mittelman, Brodaty, Wallen & Burns, ; Mittelman, Roth, Clay & Haley, ; Mittelman, Roth, Coon & Haley, ; Mittelman et al ., ; Roth, Mittelman, Clay, Madan & Haley, ). In seven studies, the caregivers were the spouses of the care recipients (Au et al .; Connell & Janevic; Drentea et al .; Mittelman et al .; Roth et al .).…”
Section: Resultsmentioning
confidence: 99%
“…Supporting caregivers' use behavioral activation may increase engagement in rewarding activities, thereby improving mood. Indeed, behavioral activation has been demonstrated to improve mood in caregivers of people with dementia (Au et al, 2014(Au et al, , 2015Lovett & Gallagher, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Concurrently, there is growing interest in using technology to address problems with access and affordability of caregiver intervention programs. A number of recent telephone-and Internet-delivered psychoeducational and self-help interventions have shown promise for improving mood and reducing burden in dementia caregivers [30][31][32][33][34][35][36]. Although these interventions have not targeted caregiver sleep per se, it would not be a far stretch to incorporate elements of CBT-I strategies or training in ABC problem-solving to help identify activators for care-receiver nighttime awakenings and to brainstorm caregiver response options.…”
Section: Caregiver Sleep Interventionsmentioning
confidence: 99%